“Control biológico de la broca del café (hypothenemus hampei), utilizando diferentes dosis del hongo beauveria bassiana en el distrito de zapatero, provincia Lamas” - Sanchez Ruiz, Maruja (2001)
The present experiment was carried out in the field of a caficultor in the smallest Populated Center San Juan of Talliquihui, understanding of Shoemaker's District, County of you Lick, Region San Martin, with the objective of evaluating the effect of the mushroom entomopatógeno Beauveria bassiana Stump CCB-LE-216 coming from Junín, to different dose 5, 1O,15 and 20 g/I multiplied in sustrato of rice in the biological control of Hypothenemus hampei and to determine the costs of application .. ' ~ . - of each dose. Which was driven totally at random under the design, with 5 treatments and 4 repetitions. The was carried out three applications to 90, 105 and 135 days after the floración; that was evaluated the Total Number of Cherry trees periodically, Number of cherry trees brocadas, Number of cherry trees with S. bassiana, Percentage of Damage for drill and Percentage of Control of the drill for 8. bassiana far branch. After the statistical analyses and interpretation you concludes that statistical difference existed in the ali number of cherry trees, but difference statistic didn't exist in the number of cherry trees brocadas and in the percentage of damage caused by drill, but increment is noticed to measure of the maturation of the fruit. B. bassiana native (witness) it caused damages to Hypothenemus hampei among 4,31% to 10,59%; the action S. bassiana introduced and B. bassiana native was compatible, reaching an it averaged of control that varied from 9,43% to 18,49%; .• , .. demonstrating that the made applications· increased among 5, 12-7,50%. The application costs varied from 324,30 to 561, 18 new suns, overcoming the dose of 20 g/I ( 4,00 Kg./ 200 1 of water), to the chemical control with Endosulfan 2,00 l/ha.